Engaging More Nurses in Cancer Preventive Care: Challenges and Opportunities. Issue 4 (July 2018) - Long, Ju; Shah, Jaymeen
Abstract : EXECUTIVE SUMMARY: Nurse-led care is crucial to improving the effectiveness of cancer prevention, as demonstrated by research. However, barriers to nurse-led cancer preventive care are still prevalent. What are the challenges that impede nurses from providing effective preventive care? How can hospital leaders address these challenges to better engage nurses in preventive care? What should be the focal areas in terms of policy changes and training programs? This article explores those questions. We examine the difficulties nurses have encountered. We identify the barriers yet to be examined extensively. Finally, we propose that many barriers can be addressed through carefully designed nurses' training programs and substantial policy changes. Our data were collected from a Nurse Oncology Education Program survey that included questions on perceived oncology knowledge, current cancer-related preventive practices, and barriers to preventive practices. We identified the barriers for the nurse population studied and opportunities to overcome these barriers.